A MASTURBAÇÃO E A ESTIMULAÇÃO SEXUAL COMO FACILITADORES DO TRABALHO DE PARTO (REMUNOM, 2025)
Childbirth is an intricate physiological process, regulated by hormonal, emotional and neurological relationships, in which oxytocin is one of the main hormones responsible for inducing and maintaining uterine contractions. In view of the growing desire to seek non-pharmacological alternatives that provide a more natural and humanized birth, this research aimed to investigate, based on recent scientific research, how masturbation and sexual stimulation can function as facilitators of labor. The investigation was carried out through a qualitative analysis, with bibliographical research of scientific sources published in the last ten years in the areas of obstetrics, human sexuality and physiology of childbirth. The research was conducted in databases such as SciELO, PubMed and LILACS, giving priority to materials with scientific evidence and practical relevance. The findings indicated that practices such as orgasm and nipple stimulation promote the release of oxytocin and endorphins, helping to accelerate contractions and relieve pain. Furthermore, explanations from pregnant women and health professionals indicate that these practices can provide relaxation, strengthen emotional bonds and a sense of control during the birth process, in line with the principles of humanized childbirth and women's autonomy. Although there is still prejudice on the subject, the results reinforce the importance of considering sexuality as a significant dimension in obstetric care, with the potential to expand the care alternatives available to pregnant women. This study also highlighted the need to overcome cultural and institutional barriers so that evidence-based practices can be incorporated in an ethical, safe and respectful manner in the context of childbirth.